Current Assessment and Management of Retinoblastoma - Hee Won Chueh (The Korean Society of Pediatric Hematology-Oncology, 2019)
Retinoblastoma is the most common intraocular malignancy in childhood. Diagnosis is currently made by ophthalmologists under general anesthesia as it is the gold standard for intraocular assessment. However, evaluations for extraocular disease are also necessary. Treatment strategies vary according to the disease status. If a single eye is involved, the treatment goal is oriented to the removal of the tumor and prevention of relapse. In bilateral retinoblastoma, the main treatment goal is to save monocular vision and save life. This article will explore the available treatment options for retinoblastoma including enucleation, radiotherapy, local therapy, intravenous chemotherapy, intra-arterial injection and intra-vitreal injections. There were recent advances in our understanding on the genetic pathophysiology of the retinoblastoma protein gene in tumorigenesis, which may help developing future treatment. Early detection of retinoblastoma is important for prolonging survival and improving quality of life.